PENDIDIKAN MULTIDISIPLIN LINTAS SEKTOR UNTUK PENANGGULANGAN STUNTING DAN KETAHANAN PANGAN DI KP. PASIR NANGKA, KEC. TIGARAKSA, KAB. TANGERANG - imam fauzy, Imam Fauzy Muldani Rachmat (LPPM Universitas Insan Pembangunan, 2024)
Stunting, caused by inadequate nutrition during a child's growth period, is a serious health issue in Indonesia with long-term impacts on the well-being of children and the community. Pasir Nangka Village, RT01 RW02, faces challenges in raising public awareness about the importance of stunting prevention and food security. Additionally, the potential of nutrient-rich local food sources has not been optimally utilized. Therefore, this community service program aims to enhance public understanding of stunting prevention and the importance of food security through a multidisciplinary approach and cross-sector collaboration. This activity is conducted by lecturers from Insan Pembangunan University, providing information on balanced nutrition, good health practices, and strategies to improve food security. Activities include site surveys, planning, and logistical coordination, involving local stakeholders such as the RT head and village chief to encourage active community participation. The results show an increased public understanding of the importance of balanced nutrition and food security, with the adoption of healthy practices in daily life reflected in positive participant responses. Recommendations for sustainable impact include further development of educational and health programs and closer cooperation with local government and educational institutions to expand the positive outcomes. Thus, this community service program is expected to make a significant contribution to improving community welfare by addressing stunting and enhancing food security in Pasir Nangka Village.